Changes in numbers of staging and wintering geese in Sweden 1977/78–2019/20 - Nilsson, Leif; Kampe-Persson, Hakon (Wildfowl, 2020)
Regular goose counts made throughout Sweden since 1977/78 show that the total numbers staging and wintering in the country have increased markedly over the decades. October totals were of 51,000 geese in 1977, rising to c. 600,000 in 2018, during which time January totals also increased from 31,000 to 252,000 birds. The greatest change recorded was for the Greylag Goose Anser anser, numbers of which rose from 20,000 to > 250,000 individuals over a 35-year period. Changes in migration and wintering habits have also been recorded, with mid-winter (January) Greylag Goose numbers now amounting to 20–33% of the September totals in recent years, illustrating increases in the proportion of the population now wintering in the country. Moreover, large numbers of Barnacle Geese Branta leucopsis have started to stage and over-winter in Sweden, and now becoming the commonest species, with 365,000 recorded in autumn 2019.